The software security decision support method development - Liqiang, Zhang; Miroshnichenko, Nataliia (Національний технічний університет "Харківський політехнічний інститут", 2022)
The actuality of the power to improve the accuracy of the results was determined in order to make a decision about the process of testing the software security. An analysis of the methods of support for making a decision was carried out. The necessity and feasibility of improving the accuracy of the results was determined in case of further software security inconsistencies in the minds of the fuzziness of input and intermediate data. With this method, on the basis of the mathematical apparatus of fuzzy logic, the method of support for making a decision about the security of software security has been developed. The main feature of this method is the synthesis of an improved method of generating the initial vibration in the process of starting a piece of neural string. Within the framework of the model, the next stages of follow-up are reached. For the mathematical formalization of the process of accepting the decision and designation of the input data, the model of forming the vector in the input data was developed. Depending on this model for shaping the input data, an anonymous sign of potential inconsistencies and undeclared possibilities of the PP is valid until the data of PVS-Studio Analysis Results. To improve the accuracy of the classification of data collected, the method of creating a piece of neural array has been improved, which is modified by the method of generating a sample, which is being developed. This generation method includes three equal generations: generation of the initial vibration, generation of the initial butt and generation of a specific value of the safety characteristic. This made it possible to increase the accuracy of classification and acceptance of the solution by 1.6 times for positive elements in the selection by 1.2 times for negative elements in the selection. To confirm the effectiveness of the development of the method of support for the decision on how to ensure software security, a ROC-analysis was carried out over the course of the above procedures. The results of the experiment confirmed the hypothesis about the efficiency of the divided method of support to make a decision about the security of PZ up to 1.2 times equal to the methods, which are based on the position of discriminant and cluster analysis.

Визначено актуальність питання підвищення точності результатів прийняття рішення щодо процесу тестування безпеки програмного забезпечення. Проведено аналіз методів підтримки прийняття рішення. Визначено необхідність і можливість підвищення точності результатів прийняття рішення при дослідженні вразливостей програмного забезпечення в умовах нечіткості вхідних і проміжних даних. З цією метою на основі математичного апарату нечіткої логіки розроблено метод підтримки прийняття рішення про безпеку програмного забезпечення. Відмінною особливістю даного методу є синтез удосконаленого способу генерації навчальної вибірки у процес навчання штучної нейронної мережі. В рамках моделювання виконані наступні етапи дослідження. Для математичної формалізації процесу прийняття рішення та визначення вхідних даних розроблено модель формування векторів вхідних даних. Відповідно до даної моделі для формування вхідних даних формується безліч ознак потенційних вразливостей та недекларованих можливостей ПЗ відповідно до даних PVS-Studio Analysis Results. Для підвищення точності класифікації оброблюваних даних удосконалено метод навчання штучної нейронної мережі, що відрізняється способом генерації вибірки, що навчається. Даний спосіб генерації включив три рівні генерації: генерація навчальної вибірки, генерація навчального прикладу і генерація конкретного значення характеристики безпеки. Це дозволило підвищити точність класифікації та прийняття рішення у 1,6 рази для позитивних елементів у вибірці та у 1,2 рази для негативних елементів у вибірці. Для підтвердження ефективності розробки методу підтримки прийняття рішення щодо безпеки програмного забезпечення проведено ROC-аналіз з виконанням відповідних процедур. Результати експерименту підтвердили гіпотезу про ефективність розробленого методу підтримки прийняття рішення про безпеку ПЗ до 1,2 рази порівняно з методами, в основі яких використовуються положення дискримінантного та кластерного аналізу.
Розробка методу підтримки прийняття рішення про безпеку програмного забезпечення
Keywords: software security inconsistency; security testing; decision support; fuzzy logic; cyberthreat; вразливість програмного забезпечення; тестування безпеки; підтримка прийняття рішення; нечітка логіка; кіберзагроза